Effects of utilizing Crumb Rubber as Aggregate in Asphalt Mixtures - Oleiwi, Safa I.; Albayati, Amjad K. (Engineering, Technology & Applied Science Research, 2024)
Experts have given much attention on the use of waste in asphalt paving because of its significance from a sustainability perspective. This paper evaluated the performance properties of asphalt concrete mixes modified with Crumb Rubber (CR) as a partial replacement for two grade sizes of fine aggregate (2.36, and 0.3 mm) at six replacement rates: 0%, 2%, 4%, 6%, 8%, and 10% by weight. Asphalt concrete mixes were prepared at their Optimum Asphalt Content (OAC) and then tested for their engineering properties. Marshall properties, fatigue, rutting, ideal CT index test, Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray (EDX) spectroscopy were deployed to examine the crystalline structure and elemental composition of the CR-modified and unmodified asphalt concrete mixtures. The results showed a difference in Marshall's characteristics. The CT index revealed that the optimum cracking tolerance was achieved with a 2% CR substitution. Wheel track test results indicated that a 4% CR addition improved the rutting resistance of the asphalt mixture. SEM and EDX analyses exhibited significant changes in microstructure and elemental composition with the addition of CR. The main findings reveal that the use of 2% CR as a partial replacement of fine aggregate contributes to the production of more durable asphalt concrete mixtures with better serviceability. However, these results are based on laboratory experiments and require field verification to ensure practical applicability and long-term performance.